Women who broke the rules : Dolley Madison - Krull, Kathleen (Krull, Kathleen. Women who broke the rules., 2015)
"Dolley Madison had a strong will and unique personality that made her one of the most memorable First Ladies. From hosting parties for Washington D.C.'s social and political elite to saving a portrait of George Washington before the British burned down the White House in the War of 1812, Dolley did it all!"--